2014
DOI: 10.1128/aac.02370-13
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis Metronidazole Resistance Is Associated with Single Nucleotide Polymorphisms in the Nitroreductase Genes ntr4 Tv and ntr6 Tv

Abstract: bMetronidazole resistance in the sexually transmitted parasite Trichomonas vaginalis is a problematic public health issue. We have identified single nucleotide polymorphisms (SNPs) in two nitroreductase genes (ntr4 Tv and ntr6 Tv ) associated with resistance. These SNPs were associated with one of two distinct T. vaginalis populations identified by multilocus sequence typing, yet one SNP (ntr6 Tv A238T), which results in a premature stop codon, was associated with resistance independent of population structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…For example, other possible mechanisms were identified, along with the presence of nitroreductase NimA-like genes, which have been implicated in metronidazole resistance in bacteria. In addition, a recent study identified single nucleotide polymorphisms (SNPs) in two nitroreductase genes (ntr4Tv and ntr6Tv) associated with resistance (Paulish-Miller et al, 2014). Consequently, further molecular studies are necessary to establish the exact mechanism of drug resistance in T. vaginalis.Overall, our findings demonstrated a high prevalence of T. vaginalis isolates infected with both M. hominis and different TVVs species.…”
mentioning
confidence: 96%
“…For example, other possible mechanisms were identified, along with the presence of nitroreductase NimA-like genes, which have been implicated in metronidazole resistance in bacteria. In addition, a recent study identified single nucleotide polymorphisms (SNPs) in two nitroreductase genes (ntr4Tv and ntr6Tv) associated with resistance (Paulish-Miller et al, 2014). Consequently, further molecular studies are necessary to establish the exact mechanism of drug resistance in T. vaginalis.Overall, our findings demonstrated a high prevalence of T. vaginalis isolates infected with both M. hominis and different TVVs species.…”
mentioning
confidence: 96%
“…We also observed transcriptional variation in paralogs of superoxide dismutase (SOD; TVAG_039980 down-regulated, TVAG_049140 up-regulated), a family of genes involved in scavenging oxygen reactive species as part of an oxygen defense mechanism in T. vaginalis previously shown to be involved in Mz resistance [24]. Finally, previous studies associated oxygen-insensitive nitroreductase (Ntr) and nitroimidazole reductase (NimA) gene mutations with Mz activation and inactivation, respectively [32,45].…”
Section: Mz Resistance Is Associated With Regulation Of Genes Involvementioning
confidence: 55%
“…95,96 Recognised problems Sequence variation (e.g., in the cryptic plasmid) may affect sensitivity. 95,96 Recognised problems Sequence variation (e.g., in the cryptic plasmid) may affect sensitivity.…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…However, the method is insensitive compared to both culture and NAAT, and requires specific microscopic expertise. 95 Further studies are warranted before molecular methods can be developed to predict T. vaginalis susceptibility to nitroimidazoles so as to inform treatment. Despite its relatively low simplicity, this takes up to 2 days to perform and sensitivity estimates fall well below that of NAAT (approximately 70% 92 ).…”
Section: Diagnosis Of T Vaginalismentioning
confidence: 99%